Students' Perceptions of KH. Ahmad Dahlan and KH. Hasyim Asy'ari i Figures in Forming Student Character at SMA NU 04 Al Ma'arif and SMA Muhammadyah 02 Boja Kendal Regency - Larasati, Putri Intan; Atno, Atno (Indonesian Journal of History Education, 2016)
This study aimed to determine understanding, perceptions, and the impact of students' perceptions on KH. Ahmad Dahlan and KH. Hasyim Asyari in building student character at SMA NU 04 Al Ma'arif and SMA Muhammadyah 02 Boja, Kendal Regency. This research was conducted using descriptive qualitative methods that produce understanding and descriptive descriptions of the research. The results showed that students 'understanding varied, as well as students' understanding in general about the biography and services of these figures. Students' understanding has differences; some students do quite well, and some are not good enough. Students' perceptions of the two characters as heroes should be exemplified in terms of their struggles and values of inherited character. The impact of students' character formation from perceptions of figures shapes religious, nationalist, character values, integrity, independence, and cooperation. Several factors influence student character formation, including environmental factors, school, and family.